Proceedings of the 6th International Conference on Human-Agent Interaction 2018
DOI: 10.1145/3284432.3284445
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Robot Gestures to Shape Users' Perception

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…Thus the degree to which a robot moves does not necessarily influence the likeability of the robot, as this is a personal preference that can vary across participants. Consistent with previous research (Deshmukh et al, 2018), there are no perceived differences in intelligence either.…”
Section: Impact Of Non-verbal Communication On the Perception Of The Robotsupporting
confidence: 91%
“…Thus the degree to which a robot moves does not necessarily influence the likeability of the robot, as this is a personal preference that can vary across participants. Consistent with previous research (Deshmukh et al, 2018), there are no perceived differences in intelligence either.…”
Section: Impact Of Non-verbal Communication On the Perception Of The Robotsupporting
confidence: 91%
“…Thus the degree to which a robot moves does not necessarily influence the likeability of the robot, as this is a personal preference that can vary across participants. Consistent with previous research [12], there are no perceived differences in intelligence either.…”
Section: Impact Of Non-verbal Communication (Nvc) On the Perception Osupporting
confidence: 91%
“…On the other hand, human empathy toward the agent was maintained in the presence of agent expression. Studies by Beck et al [41] and Deshmukh et al [47] have shown that agent expressions (gestures and comments) can enhance understanding from humans, and our study also elicited human empathy toward the agent.…”
Section: B the Influence Of The Task And The Importance Of The Agent'...supporting
confidence: 70%
“…They measured children's perceptions of social presence, engagement, and social support and found that the empathy model developed had a positive impact on the long-term interaction between the child and the robot. Deshmukh et al [47] analyzed the relationship between the way robots gesture and the way those gestures are perceived by human users. In particular, they investigated how changing the amplitude and speed of a gesture affects the Godspeed score given to that gesture.…”
Section: Empathy In Human-agent Interactionmentioning
confidence: 99%